2020
DOI: 10.1016/j.hrthm.2020.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Cryoballoon ablation of pulmonary veins for persistent atrial fibrillation: Results from the multicenter STOP Persistent AF trial

Abstract: BACKGROUND Pulmonary vein isolation (PVI) is the cornerstone of catheter ablation to treat patients with symptomatic drugrefractory atrial fibrillation (AF).OBJECTIVE The purpose of this study was to assess the safety and efficacy of PVI using the cryoballoon catheter to treat patients with persistent AF.METHODS STOP Persistent AF (ClinicalTrials.gov Identifier: NCT03 012841) was a prospective, multicenter, single-arm, Food and Drug Administration-regulated trial designed to evaluate the safety and efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
119
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 115 publications
(143 citation statements)
references
References 20 publications
(42 reference statements)
13
119
0
1
Order By: Relevance
“…World‐wide safety of AF ablation has not been published since 2010, in which outcomes after AF ablation performed by radiofrequency ablation catheters were estimated via a voluntary survey 16 . Here, the world‐wide safety profile of cryoballoon ablation procedures conducted according to standard practice at 93 unique global centers (3.4% serious procedure‐ and 1.5% serious device‐related adverse event rate) aligns with smaller, controlled cryoballoon ablation trials and region‐specific observational registries 2‐4,17‐20 . Despite larger LA diameters and generally higher rates of comorbidities in the PsAF cohort compared to the PAF cohort, adverse event rates were similar for both groups treated in this registry.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…World‐wide safety of AF ablation has not been published since 2010, in which outcomes after AF ablation performed by radiofrequency ablation catheters were estimated via a voluntary survey 16 . Here, the world‐wide safety profile of cryoballoon ablation procedures conducted according to standard practice at 93 unique global centers (3.4% serious procedure‐ and 1.5% serious device‐related adverse event rate) aligns with smaller, controlled cryoballoon ablation trials and region‐specific observational registries 2‐4,17‐20 . Despite larger LA diameters and generally higher rates of comorbidities in the PsAF cohort compared to the PAF cohort, adverse event rates were similar for both groups treated in this registry.…”
Section: Discussionmentioning
confidence: 85%
“…Similar to controlled clinical trials, patients with PsAF had baseline characteristics indicative of more advanced AF disease progression and a higher rate of comorbidities than enrolled patients with PAF 3,4 . Regardless of AF classification, standard‐of‐care approaches to treat patients with AF resulted in a consistent and efficient procedure with an average total procedure time of 82 minutes.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Since its introduction in 2007, cryoballoon (CB) ablation has emerged as a valid alternative to the point‐to‐point technique with radiofrequency for achieving PVI 3 and this reproducible and rapid technique has become established as a major technique for index procedures in paroxysmal and persistent AF ablation. Indeed, several landmark studies have demonstrated the feasibility, safety, and efficacy of the CB ablation for both paroxysmal and persistent AF 3‐7 . Compared with radiofrequency, the CB technique offers several advantages such as shorter procedure duration, shorter learning curve and a higher degree of reproducibility 8 .…”
Section: Introductionmentioning
confidence: 99%